ALLOPLASTIC IMPLANTS FOR RHINOPLASTY: A SYSTEMATIC REVIEW AND META-ANALYSIS OF CLINICAL OUTCOMES AND COMPLICATIONS - Cikita, Rafeni Bunga; Nataadmaja, Beta Subakti (Folia Medica Indonesiana, 2025)
Alloplastic implants emphasize the importance of a comprehensive understanding of both clinical and histological aspects, which are attributed to enhancing patient satisfaction and surgical success rates. The study aims to assess the viability of different implant materials and their related risks over time. A systematic literature search was conducted across multiple databases, including PubMed, Cochrane, and EBSCOhost, to identify 79 records. After eliminating duplicates and applying specific inclusion and exclusion criteria, four new studies were included for evaluation, focusing on postoperative outcomes related to alloplastic implants in rhinoplasty. Late-onset inflammation in non-healthy capsules required removal and showed histological damage. One study also found increased infection rates in soft implants and aesthetic adjustment concerns with firm implants. Other research reported Medpor implants’ long-term durability, but malposition and infection. Silicone implants had a 10% infection rate and 30% displacement rate, while Medpor(R) had contracture and contour difficulties. Overall, complications vary based on implant type and patient factors. The review emphasizes the importance of using the right implant materials and surgical methods to reduce problems. It advocates for further research into alternative materials and personalized approaches to enhance patient outcomes in rhinoplasty procedures.